Exploring the interaction between social norms and perceived justice of wind energy projects: a qualitative analysis. Issue 2 (4th March 2023) - Karakislak, Irmak; Hildebrand, Jan; Schweizer-Ries, Petra
ABSTRACT: The deployment of wind energy projects (WEP) within the process of energy transition changes energy landscapes and daily living environments. With regard to social acceptance as one social response towards WEP, the role of different aspects of justice (i.e. procedural, distributive, recognition) has been discussed. This study highlights the importance of social norms and their influence on perceived justice regarding WEP, which has been neglected in the literature so far. The relationship between social norms and perceived justice is explored as a conceptual framework through a systematic literature review and expert interviews. This framework aims to explain how social norms and their relationship with justice are defined, interlinked and how they affect perceptions of WEP. The results argue that social norms surface in situations where all the key elements of a project are decided without public impact. Thus, norms of fairness emerge under uncertain situations with the influence of similar emotions within groups. Moreover, social norms and perceived justice would explain several responses, such as local conflicts, or the motivation to further develop WEP. This study concludes by discussing the applicability of the framework, which needs further analysis as an analytical tool and deeper empirical investigation.